Continuous flow nitration in miniaturized devices - Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2014)
This review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitations and applicability of the information towards scale-up. Selected recent patents that disclose scale-up methodologies for continuous flow nitration are also briefly reviewed.
Keywords: continuous flow; flow chemistry; microreactors; nitration; nitric acid; Tubular reactor